Pengaruh Literasi Keuangan Syariah, Aktivitas Galeri Investasi Syariah, Modal Minimal, dan Religiusitas Terhadap Minat Investasi Mahasiswa di Pasar Modal Syariah - musyafa' musyafa' (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study is to measure and determine the effect of Islamic financial literacy, Sharia Investment Gallery (GIS) activities, minimum capital, and religiosity on student interest in investing in the Islamic capital market. This research uses mixed method research (quantitative research and qualitative research). The population used is students who are registered as investment account makers in 2020 s.d. 2021 through the Sharia Investment Gallery of the Nahdlatul Ulama Islamic University (UNISNU) Jepara, totaling 467 students. Sampling based on non-probability sampling with the number of samples using simple random sampling technique with the calculation of the Slovin formula, obtained 82 respondents. Data obtained from observations, questionnaires, and indepth interviews. The questionnaire was measured based on a Likert scale and using SPSS version 25 software. The results of this study indicate that partially Islamic financial literacy tends to have an influence. GIS activities, minimal capital, and religiosity partially have a positive and significant effect on student investment interest. Simultaneously, the variables of Islamic financial literacy, Sharia Investment Gallery activity, minimal capital, and religiosity have a positive and significant effect on student investment interest in the Islamic capital market